Comprehensive Investigation of MXene and Cassava Tubers-Bamboo Stems Activated Carbon Electrodes: Configuration-Dependent Supercapacitor Performances - Nuviya Illa Muthi Aturroifah; Markus Diantoro; Nasikhudin Nasikhudin (Universitas Negeri Malang, 2024)
This study explores the structural, morphological, and electrochemical characteristics of supercapacitor active materials derived from MXene (Ti3C2Tx) and activated carbon (AC) synthesized from cassava tubers and bamboo stems. The etching process using HF effectively converted the MAX phase into MXene, confirmed by the disappearance of the (104) diffraction peak and the shift of the (002) peak to a lower diffraction angle, indicating increased interlayer spacing due to aluminum removal and intercalation of functional groups and water molecules. SEM analysis revealed that MXene exhibits thinner layered structures with reduced crystallite size (112.65-8.13 nm), confirming the formation of a highly conductive two-dimensional structure. Meanwhile, AC cassava tubers-bamboo stems presented an amorphous graphitic structure with a three-dimensional porous morphology resembling a sunflower pattern and an average pore diameter of 3.52 µm, which enhances ion transport and active surface area. Electrochemical performance evaluation demonstrated that the AC-MXene-Al Foil//AC-MXene-Cu Foil configuration achieved the highest performance, with a specific capacitance of 46.201 Fg-1, energy density of 5.770 Whkg-1, and power density of 18.996 Wkg-1. Dunn method analysis revealed that the charge storage mechanism is primarily surface capacitive. These results demonstrate the promising potential of biomass-derived AC/MXene composites for high-performance and sustainable energy storage applications.